On the causative and passive morphology in Japanese and Korean - Aoyagi Hiroshi (De Gruyter, 2021)
Drawing on the layered verb phrase hypothesis, the unexpected adversity imposed on the subject of causative–passives in Japanese will be explained by the loci of -sase and -rare, both of which may instantiate more than one functional heads. This hypothesis also gives an account of the marginal status of passive–causatives whose passivized subject (=causee) is animate. Turning to Korean, /Hi/ is univocally causative, and its apparent use as passive is the result of Voice–Cause bundling. Furthermore, the possible and impossible uses of /Hi/ and /Hu/ as passive morphology result from their selectional properties.